1998
DOI: 10.1074/jbc.273.3.1689
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Actin-binding Protein 280 in Integrin-dependent Mechanoprotection

Abstract: To survive in a mechanically active environment, cells must adapt to variations of applied membrane tension. A collagen-coated magnetic bead model was used to apply forces directly to the actin cytoskeleton through integrin receptors. We demonstrate here that by a calcium-dependent mechanism, human fibroblasts reinforce locally their connection with extracellular adhesion sites by inducing actin assembly and by recruiting actinbinding protein 280 (ABP-280) into cortical adhesion complexes. ABP-280 was phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
185
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(194 citation statements)
references
References 44 publications
9
185
0
Order By: Relevance
“…Previous studies have suggested that mechanical force application to integrins can activate mechanosensitive ion channels and trigger Ca 2+ entry into cells. Ca 2+ entry may influence cell mechanics by modulating cytoskeletal structure or contractility (Glogauer et al, 1997(Glogauer et al, , 1998. Ca 2+ -activated proteases, such as calpain are associated with FAs (Glading et al, 2002).…”
Section: Cellular Mechanotransductionmentioning
confidence: 99%
“…Previous studies have suggested that mechanical force application to integrins can activate mechanosensitive ion channels and trigger Ca 2+ entry into cells. Ca 2+ entry may influence cell mechanics by modulating cytoskeletal structure or contractility (Glogauer et al, 1997(Glogauer et al, , 1998. Ca 2+ -activated proteases, such as calpain are associated with FAs (Glading et al, 2002).…”
Section: Cellular Mechanotransductionmentioning
confidence: 99%
“…Outside the nervous system, one of the most prominent editing-induced recoding events occurs in filamins. Filamins are actin-binding proteins which link the actin network to cellular membranes and transmembrane receptors [9]. The interactions with a plethora of proteins link filamins to different cellular processes, such as signalling, transcriptional regulation, migration, and tissue organization [10].…”
Section: Introductionmentioning
confidence: 99%
“…First, it may be due to an elastic response of the actin filaments [25]; second, it may be attributed to the changes in the cellular activities such as enhancement of the contractile force and reinforcement of stress fibers [10,26]. Janmey et al investigated the elastic property of an actin matrigel and showed that more than 10% of the strain was required to yield a 2-fold increase in stress [27].…”
Section: Discussionmentioning
confidence: 99%